Building Information Modelling (BIM) and Occupational Safety in Infrastructure Projects - Ammad, S. (Institute of Electrical and Electronics Engineers Inc., 2021)
The usage of new technology has drastically altered the way, work is handled and performed out in recent times. Building Information Modelling (BIM) is increasingly being used in infrastructure projects to boost the effectiveness of a variety of tasks. The purpose of this study is to extract previous knowledge regarding BIM and occupational safety in infrastructure projects. Papers published in the period going from 2008 to 2019 were selected a total number of 50 studies were selected. All studies were targeting BIM, safety adoption, and accidents related to construction infrastructure projects. This paper helps to identify the critical success factors for safety efficiency application in the infrastructure project. New type of policies related to Covid-19 are also incorporated in the construction industry which also set new standards and operating procedures to work safely in the pandemic conditions. Two main group factors were identified safety training, and safety management a networking analysis between all the factors identified from previous studies was run. This networking shows a link of importance between each other and how each cluster overlaps the sub-factors of other clusters. Finally using word cloud analysis, it was possible to identify the top five keywords from the extracted factors. Â© 2021 IEEE.